2007
DOI: 10.1159/000100795
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Intra-Amniotic Maternal Hemorrhage in Term Pregnancy

Abstract: Introduction: Intra-amniotic maternal hemorrhage is a rare condition, hard to differentiate from some other conditions in pregnancy. We report an unusual case of intra-amniotic maternal hemorrhage in term pregnancy ending in urgent cesarean section, identified on ultrasound examination. Case Report: A 24-year-old female (gravida 3, para 2, abortion 0) was admitted to hospital at 40 weeks’ gestation for collapse and general weakness. Her blood pressure was 90/60 mm Hg, pulse 112 bpm, temperature 36°C. The fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…A source for hemoglobin in amniotic fluid can be intra-amniotic bleeding prior to amniocentesis, although this condition is rare14;15 and may derived from the maternal15-17 or fetal18 circulation. Maternal intra-amniotic bleeding has been reported in association with placental abruption,19;20 circumvallated placenta,15 as well as PTL15;16 with clinical14 or histological chorioamnionitis 16.…”
Section: Commentmentioning
confidence: 99%
“…A source for hemoglobin in amniotic fluid can be intra-amniotic bleeding prior to amniocentesis, although this condition is rare14;15 and may derived from the maternal15-17 or fetal18 circulation. Maternal intra-amniotic bleeding has been reported in association with placental abruption,19;20 circumvallated placenta,15 as well as PTL15;16 with clinical14 or histological chorioamnionitis 16.…”
Section: Commentmentioning
confidence: 99%
“…She developed haemorrhagic shock and underwent immediate caesarean delivery. The placental histological examination was normal with no evidence of an abruption, but there was a 20 cm diameter 450 g blood clot detected 8…”
Section: Discussionmentioning
confidence: 97%
“…Placental histological analysis revealed chorioamnionitis 7. Finally, intra-amniotic haemorrhage has also presented with maternal collapse, tachycardia, hypotension and anaemia at 40 weeks of gestation 8. Ultrasound examination showed a live, well-grown fetus with a large intra-amniotic homogenous echogenic mass (120×80 mm).…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few reports in the literature on intra-amniotic hemorrhages, which are not related to amniocentesis ( table 1 ). Sijanovic et al [2] reported on a woman whose presenting symptoms were weakness and tachycardia. Witter and Sanders [3] reported on maternal hemorrhage into the amniotic fluid associated with chorioamnionitis, and Kurata et al [4] described a case of a symptomatic anemic patient with 'pseudo polyhydramnios' and a clot identified by an ultrasound.…”
Section: Discussionmentioning
confidence: 99%